Hungarian Monitoring, 12 October 1990 . [Magyar rádiófigyelő], 1990. október 12 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Scandal following publication of a book of exposures in France - Estonian economic and financial problems - Presence of Soviet troops in Germany - Attempted attack in Cairo Domestic Affairs: - Antall-Lubbers in talks in Holland - Groundless charge of antisemitism in Parliament - Hungary will leave the Warsaw Pact at the end of next year - On the transformation of the criminal law code Economy: - Hungarian National Bank receives Austrian bank loan - Capital shortages at small enterprises - Domestic trade privatization Külpolitika: - Leleplező botránykönyv Franciaországban - Észt gazdasági és pénzügyi nehézségek - Szovjet csapatok jelenléte Németországban - Kairói merénylet Belpolitika: - Antall-Lubbers tárgyalás Hollandiában - Alaptalan antiszemitizmus-vád a parlamentben - Magyarország a jövő év végén kilép a Varsói Szerződésből - A Btk. Átalakításáról Gazdaság: - A Magyar Nemzeti Bank osztrák bankkölcsönt kapott - Tőkehiány a kisvállalkozásoknál - Belkereskedelmi privatizáció